Open innovation: The missing nexus between entrepreneurial orientation, total quality management, and performance of SMEs - Muzaffar Asad; Muhammad Uzair Asif; Mohammed Ali Bait Ali Sulaiman; Mir Shahid Satar; Ghadah Alarifi (Journal of Innovation and Entrepreneurship, 2023)
Drawing upon the theoretical foundations of the resource-based view, the current research aims to examine the mediating role of open innovation between entrepreneurial orientation, total quality management, and SMEs performance. Open innovation is not new, but SMEs operating in the developing economies are unaware of it importance and need. A structural equation model was used in the study to evaluate the relationships between the data collected from 270 SMEs with the help of adopted questionnaires. The results confirmed the impact of entrepreneurial along with total quality management on open innovation as well as the performance of SMEs. Second, the indirect impact of entrepreneurial orientation along with total quality management via open innovation has also been established which is proven as significant. Owners and managers of SMEs should consider customer-driven practices in an entrepreneurial manner to achieve elevated levels of performance based on the study's findings.
Keywords: 650; Entrepreneurial orientation; Open innovation; SMEs; Total quality management